Conformationally Confined Emissive Cationic Macrocycle with Photocontrolled Organelle‐Specific Translocation. Issue 23 (17th June 2022) - Dong, Xiaoyun; Dai, Xianyin; Li, Guorong; Zhang, Ying‐Ming; Xu, Xiufang; Liu, Yu
Abstract: The optimization of molecular conformation and aggregation modes is of great significance in creation of new luminescent materials for biochemical research and medical diagnostics. Herein, a highly emissive macrocycle (1 ) is reported, which is constructed by the cyclization reaction of triphenylamine with benzyl bromide and exhibits very distinctive photophysical performance both in aqueous solution and the solid state. Structural analysis reveals that the 1 can form self‐interpenetrated complex and emit bright yellow fluorescence in the crystal lattice. The distorted yet symmetrical structure can endow 1 with unique two‐photon absorption property upon excitation by near‐infrared light. Also, 1 can be utilized as an efficient photosensitizer to produce singlet oxygen ( 1 O2 ) both in inanimate milieu and under cellular environment. More intriguingly, due to the strong association of 1 with negatively charged biomacromolecules, organelle‐specific migration is achieved from lysosome to nucleus during the 1 O2 ‐induced cell apoptosis process. To be envisaged, this conformationally confined cationic macrocycle with photocontrolled lysosome‐to‐nucleus translocation may provide a feasible approach for in situ identifying different biospecies and monitoring physiological events at subcellular level. Abstract : A triphenylamine‐based tetracationic macrocycle not only exhibits distinctive photoluminescence behaviors both in solution and solid state via the conformation confinement effect but also undergoes a photocontrollable lysosome–nucleus translocation in the cell apoptosis process induced by the photosensitized singlet oxygen.